PENGARUH KINERJA KEUANGAN DAN PERTUMBUHAN POTENSIAL TERHADAP KEBIJAKAN DIVIDEN - Putri, Rosyida Sutrisno; Mildawati, Titik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the influence of liquidity, leverage, profitability, and potential growth to the dividend policy. Liquidity, in this research, is measured by using current ratio (CR) formula, leverage is mesured by using debt to equity ratio (DER), profitability is measured by using return on equity (ROE), potential growth (PP) is measured by using potential growth formula and dividend policy is measured by using dividend payout ratio formula (DPR). The population is all companies which engage in the field of consumers and goods sector manufacturing industries which are listed in Indonesia Stock Exchange (IDX) in 2011-2014 periods. The total samples are 15 companies which have been determined by using purposive sampling. The data analysis instrument in this research is the multiple linear regressions analysis. The analysis techniques have been carried out by using F statistic test and t statistic test. The result of the research shows that current ratio or liquidity does not have any influence to the dividend policy. Leverage, in this case DER, does not have any influence to the dividend policy. Return on equity or profitability gives influence to the dividend policy. Potential growth gives influence to the dividend sharing policy of the company.Keywords: Liquidity, leverage, profitability, potential growth, dividend policy.